DIGITAL MARKETING COMMUNICATION MODEL TO PERSUADE QRIS TRANSACTION IN @tmrwindonesia INSTAGRAM ACCOUNT - Susilo, Daniel (Penerbit Lafadz Jaya, 2023)
In the current digital age, the way we interact with money has fundamentally shifted. Traditional forms of currency are increasingly being replaced by digital means, especially among younger generations such as Millennials and Generation Z. This paper explores this trend within the context of Indonesia's successful implementation and management of a digital payment system known as Quick Response Code Indonesian Standard (QRIS), which is setting a precedent for other countries to follow. The study employs Klaus Krippendorf's content analysis methodology to evaluate data derived from @tmrwindonesia, a popular social media account that encourages Indonesians to adopt QRIS. By examining posts, comments, shares, and likes on this platform over a one-year period (2023-2024), we seek to understand how social media influences the adoption rate and perception of QRIS among these demographics. Preliminary findings suggest that there is a positive correlation between exposure to @tmrwindonesia's content and increased use of QRIS among Millennials and Gen Z. The analysis also reveals that users view this innovative digital payment system as an important national achievement that bolsters their national identity. These findings have significant implications for policymakers and businesses alike. For policymakers, understanding how younger generations perceive and use digital currencies can inform future policy directions in financial technology (Fintech). For companies operating in Indonesia or looking to expand into Southeast Asian markets, these insights can guide strategic decisions about incorporating or promoting QRIS as part of their business models.